Environmental friendly energy resources improving air quality in urban area - Kaczmarczyk, Michał; Sowiżdżał, Anna (Energy reports, 2024)
The article concerns a very important issue related to the air quality in Kraków, a historic city with a rich history and cultural tradition. Kraków is the capital of the Małopolska Voivodeship, located in southern Poland. Due to the common phenomenon of smog in winter and the related problem of significant exceedances of permissible air pollutants, Kraków was the first city in Poland which implemented a complete ban on the combustion of solid fuels (coal, wood and also all types of biomass). It is allowed to use only district heat, gaseous fuels, light fuel oil, electricity and renewable energy sources as heat pumps, solar collectors and photovoltaics. The article attempts to analyze the results of air quality tests in the period after the implementation of restrictions on the type of energy sources used in relation to the previous years. The starting point for this analysis is the presentation of emissions of combustion products of energy carriers with various calorific values in heating devices with various energy efficiency. Environmental aspects are also analyzed, such as average annual temperatures, wind speeds and directions, precipitation, and the number of days with fog. Thanks to this, the picture of the changes introduced in Kraków becomes complete and allows you to understand the environmental effects that have occurred. The analysis of air quality was carried out with regard to six pollutants: TSP (total suspended particulate), PM10 and PM2.5 particulate matter, benzo(a)pyrene, sulfur dioxide (SOx), and nitrogen oxides (NOx). Additionally equivalent emission has been calculated. The obtained results indicate an improvement in air quality in relation to the previous heating periods, which allows to draw a conclusion that regulatory actions such as a ban on the burning of solid fuels was justified and that this sector (individual heat generation) has a significant impact on the state of the environment. A significant reduction in all analyzed pollutants – TSP, PM10 and PM2.5, B(a)P and SOx is evident, and the only the exception is NOx.